PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL - Imam Makhali; Anggara Seta Aji (Lembaga Marwah Rakyat, 2022)
This study discusses legal protection for victims of sexual violence. The formulation of this research is: what is the form of legal protection for workers who are victims of sexual harassment cases and what are the legal consequences for perpetrators of sexual harassment when viewed from the Labor Law and Criminal Law in Indonesia. The method used in this research is normative research. The result of this research is that the legal protection of workers from acts of sexual harassment is regulated in various existing regulations, including those that directly provide protection are Law no. 13 of 2003 concerning manpower, Law no. 2 of 2004 concerning Settlement of Industrial Relations Disputes and the Criminal Code, the procedure for resolving cases of sexual harassment in the workplace uses Law no. 13 of 2003 concerning Manpower, namely by deliberation, negotiation, if there is no agreement then the last step is to file a claim for layoffs.